Major Metabolites and Microbial Community of Fermented Black Glutinous Rice Wine With Different Starters - Jiang, Li; Su, Wei; Mu, Yingchun; Mu, Yu (Frontiers in Microbiology, 2020)
Black glutinous rice wine (BGRW) is a traditional Chinese rice wine that is brewed using multiple strains. However, the roles of these microorganisms, particularly their contributions to aroma formation, are poorly understood. Accordingly, the main goal of this study was to determine the microbial communities and major metabolites of different traditional fermentation starters. Anshun starter (AS) and Xingyi starter (XY) were used for BGRW to provide insight into their potential contributions to the variation in flavor and aroma. High-throughput sequencing of the microbial community using the Illumina MiSeq platform revealed significant differences during fermentation between the two starter groups. Pediococcus, Leuconostoc, and Bacillus were the dominant bacterial genera in the AS group, whereas Leuconostoc, Pediococcus, and Gluconobacter were the dominant genera in the XY group. In addition, Rhizopus, Saccharomyces, and Saccharomycopsis were the predominant fungal genera detected in both samples. The major metabolites in the two groups were identified by high-performance liquid chromatography and headspace-solid-phase microextraction gas chromatography-mass spectrometry. A total of seven organic acids along with 47 (AS) and 43 (XY) volatile metabolites were detected, among which lactic acid was the primary organic acid and esters was the largest group in both types of wine. Principal components analysis further revealed significant differences in the dynamic succession of metabolites between the two samples. Correlation analysis showed that 22 and 17 microorganisms were strongly correlated with the production of major metabolites in AS and XY, respectively. Among them, Pediococcus, Leuconostoc, Lactobacillus, Lactococcus, and Streptococcus were shown to play crucial roles in metabolite synthesis. Overall, this study can provide a valuable resource for the further development and utilization of starters to improve the aromatic quality of BGRW.